Trends in Mathematics towards Enriched Society Today: Exploring the Role of Mathematics in Interdisciplinary Research for an Enriched Society (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper makes an attempt to study a role of mathematics as the current thinking of collaborative approach to inter-disciplinary trends towards enriched society in the 21st century. It begins with trends of applications of the 20th century bridging the line of inter-disciplinary research. It tries to address the changes in mathematics applications as a result of the modern approach to mathematics and discoveries in other fields such as computer, socio-economic, medical science, biological science, industries, business, environmental sciences, etc. The paper also highlights what are the hindrances in bridging the Integrated Knowledge towards enriched society suggesting Fuzzy Mathematics as a new area where mathematics is emerging as vital trends with greater opportunities for inter disciplinary research.